CHANGING PATTERN OF FABRICATED INJURIES IN LARKANA REGION - Khichi, Zawar Hussain; Humayun, Muhammad; Prithiani, Kanwal Kumar N; Akbar, Qazi Muhammad; Kaheri, Ghulam Qadir (Journal of Ayub Medical College Abbottabad, 2009)
Background: Man has been egotist by nature and from Ancient time man has been endeavouring to bring under power other human beings. With the passage of time and growth of civilization this trend has been increased. Now there are more dangerous ways of violence and torture in use for twisting and turning people around. Inflection of fabricated injuries is one of the ways for fulfilment of his lust. Incidence of fabricated injuries is related with crime rate in any society, and this practice is carried out through out the world. Fabricated Injury is a major problem which forensic expert/causality medical officer face during their duty. Very little literature is available regarding study of fabricated injuries and no authentic criteria has so for been developed for labelling an injury as fabricated one. Methodology: The present study is about 130 challenged medico-legal cases in Larkana Division which were studied in special medical board held in the Department of Urology Chandka Medical College Larkana. Out of 130 cases 50 were proved to be fabricated. Results: The total number of challenged cases was 130, out of these 50 (38.46%) cases were of fabricated injuries. Out of 50 fabricated cases, 46 (92%) were males and 4 (8%) were female, thus the male to female ratio was approximately 11:1. Maximum cases (25) were from Larkana District, 15 cases were from Shikarpur and 10 cases from Jacobabad. The majority of fabricated injuries from Larkana District were nose injuries as out of 25 fabricated injuries from Larkana district 10 were nasal injuries, while from district Jacobabad and Shikarpur there was no nasal fabricated injury. Conclusion: Most of the fabricated injuries are caused on accessible part of the body like arms, legs, abdomen, chest etc. The pattern of fabricated injuries is changing in Larkana District as out of 25 fabricated injuries in this district 10 were nasal injuries while in District Jacobabad and Shikarpur there was no nasal fabricated injury. Keywords: Ancient, Fabricated, Injuries, Torture, Endeavouring, Authentic, Egotist